Mesenchymal stromal cells-derived extracellular vesicles alleviate systemic sclerosis via miR-29a-3p. Issue 121 (July 2021) - Rozier, Pauline; Maumus, Marie; Maria, Alexandre Thibault Jacques; Toupet, Karine; Lai-Kee-Him, Joséphine; Jorgensen, Christian; Guilpain, Philippe; Noël, Danièle
Abstract: Systemic sclerosis (SSc) is a potentially lethal disease with no curative treatment. Mesenchymal stromal cells (MSCs) have proved efficacy in SSc but no data is available on MSC-derived extracellular vesicles (EVs) in this multi-organ fibrosis disease. Small size (ssEVs) and large size EVs (lsEVs) were isolated from murine MSCs or human adipose tissue-derived MSCs (ASCs). Control antagomiR (Ct) or antagomiR-29a-3p (A29a) were transfected in MSCs and ASCs before EV production. EVs were injected in the HOCl-induced SSc model at day 21 and euthanasized at day 42. We found that both ssEVs and lsEVs were effective to slow-down the course of the disease. All disease parameters improved in skin and lungs. Interestingly, down-regulating miR-29a-3p in MSCs totally abolished therapeutic efficacy. Besides, we demonstrated a similar efficacy of human ASC-EVs and importantly, EVs from A29a-transfected ASCs failed to improve skin fibrosis. We identified Dnmt3a, Pdgfrbb, Bcl2, Bcl-xl as target genes of miR-29a-3p whose regulation was associated with skin fibrosis improvement. Our study highlights the therapeutic role of miR-29a-3p in SSc and the importance of regulating methylation and apoptosis. Graphical abstract: Image 1 Highlights: Extracellular vesicles released by MSC recapitulate their therapeutic effect in SSc. MiR-29a-3p is a key regulator of the therapeutic effect of MSCs in SSc. MiR-29a-3p targets fibrotic, remodeling, apoptotic, epigenetic processes. Novel targets of miR-29a-3p, namely Dnmt3a and Pdgfrbb, have been identified in SSc.